Prevention Of Election Violations In 2024 In North Jakarta City Bawaslu Using A Participative Oversight Model - Ismi, Aulia Nurul; Jannah, Dejahave Al (UNIVERSITAS PAKUAN, 2024)
General elections are a very important pillar of democracy in a government system based on the will of the people. Elections are the primary way in which citizens participate in the selection of their representatives and leaders, and therefore, electoral integrity is of paramount importance to ensure that citizens have an equal opportunity to express their political preferences. However, elections do not always run smoothly and without problems. One of the main challenges in general elections is election violations, which can include various forms, such as negative campaigning, vote manipulation, and non-compliance with election rules. The qualitative research method applied in this research, as explained by Bogdan and Taylor, involves descriptive data collection procedures in the form of written or spoken words from people and observed behavior. Data was obtained through observation and interviews, then processed into words that were easy to understand. This approach provides a deep understanding of the context and nuances contained in North Jakarta City Bawaslu's qualitative data and also presents program innovations, such as supervision classes, supervision patrols, door to door, and road shows, to support electoral education. Although innovative, ongoing evaluation is required to ensure their effectiveness, involving collaboration with relevant parties and adequate allocation of resources. The supervisory models applied include widespread, limited and issue-based. Even though various model programs have been designed, evaluations show that community involvement is still low. Therefore, efforts are needed to increase public awareness, their role as informants and reporters, as well as preventive measures against election violations.